2004
DOI: 10.1002/cmr.a.20012
|View full text |Cite
|
Sign up to set email alerts
|

On experimental aspects of electrophoretic NMR

Abstract: Artefacts in electrophoretic NMR experiments are investigated in detail. We identify electroosmosis, sample heating, and gas development on the electrodes as main error sources and suggest experimental strategies and setups to suppress their influence on the monitored electrophoretic mobilities. We hereby demonstrate essentially artefact-free experiments up to currents and electric fields 3 mA and 70 V/cm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 40 publications
0
55
0
Order By: Relevance
“…Subtracting this from the phase shift observed for charged species, one then arrives at the correct electrophoretic phase information. Note that the same correction procedure also applies for stimulated-echo-type experiments such as EDSTE [16]. While suppression of thermal convection is possible by alternation the electric polarity, that strategy does not work for suppressing electro-osmosis since that flow pattern alters direction in the same way as electrophoresis does.…”
Section: Phase Detection and Phase Difference Compensationmentioning
confidence: 91%
See 2 more Smart Citations
“…Subtracting this from the phase shift observed for charged species, one then arrives at the correct electrophoretic phase information. Note that the same correction procedure also applies for stimulated-echo-type experiments such as EDSTE [16]. While suppression of thermal convection is possible by alternation the electric polarity, that strategy does not work for suppressing electro-osmosis since that flow pattern alters direction in the same way as electrophoresis does.…”
Section: Phase Detection and Phase Difference Compensationmentioning
confidence: 91%
“…We also found that eNMR experiments based solely on the basic approach [27] suggested by He and Wei (and on its extension to stimulated echo experiments [16]) were not satisfactory in a majority of our past experiments. This might partly be because thermal convection also has a finite build-up time and will likely be stronger during the second of the two electrophoretic pulses.…”
Section: Cpmg-like Enmr Experimentsmentioning
confidence: 94%
See 1 more Smart Citation
“…The second problem may be tackled by coating the interior of the sample tubes with a suitable polymer. Detailed discussions of the method and the problems associated with it can be found in Johnson and He and Pettersson et al (81,91).…”
Section: Studies Of Surfactant-polymer Interactionsmentioning
confidence: 99%
“…Proton ENMR measurements were performed on protons in aqueous solutions of crown ethers and alkali metal chlorides at 298 K. The studies were made on a Bruker 200 MHz DMX spectrometer using a U-tube and general procedures as described by Pettersson et al 38 A double-stimulated-echo pulse sequence including electrophoretic pulses was applied with  D 250 ms, υ D 1 ms and g D 0.22 T m 1 . The voltage (U) was increased linearly from zero to 2 kV in eight steps, while keeping other parameters constant during measurements.…”
Section: Enmr On Crown 18-6 and 15-5 Systemsmentioning
confidence: 99%